Giant Cell Fibroma in a Two-Year-Old Child - Anna Carolina Volpi Mello-Moura; Ana Maria Antunes Santos; Gabriela Azevedo Vasconcelos Cunha Bonini; Cristina Giovannetti Del Conte Zardetto; Cacio Moura-Netto; Marcia Turolla Wanderley (Hindawi Limited, 2016)
The giant cell fibroma is a benign nonneoplastic fibrous tumor of the oral mucosa. It occurs in the first three decades of life in the mandibular gingiva, predominantly, showing predilection for females. This article reports a case of giant cell fibroma in a 2-year-old girl, which is an uncommon age for this lesion. The patient was brought for treatment at the Research and Clinical Center of Dental Trauma in Primary Teeth, where practice for the Discipline of Pediatric Dentistry (Faculty of Dentistry, University of São Paulo, Brazil) takes place. During clinical examination, a tissue growth was detected on the lingual gingival mucosa of the lower right primary incisors teeth. The lesion was excised under local anesthesia and submitted to histological examination at the Oral Pathology Department of the Faculty of Dentistry, University of São Paulo, which confirmed the diagnosis of giant cell fibroma. There was no recurrence after 20 months of monitoring. This instance reinforces the importance of oral care from the very first months of life in order to enable doctors to make precocious diagnosis and offer more appropriate treatments for oral diseases, as well as to promote more efficient oral health in the community.